Humanism and Professionalism in Police Reform: A Human Rights-Based Approach to Law Enforcement - Saragih, Apri Cuanra; Berutu, Sigar P. (Universitas Brawijaya, 2025)
This study departed from the persistent shortcomings in police practices that prioritise the protection of human rights, alongside the prevailing reliance on repressive approaches in law enforcement. Prior studies by Agus Raharjo and Angkasa (2011) as well as Abiezer Manora Purba (2024) highlight the importance of police ethics and professionalism, but without offering a comprehensive integration of institutional reform strategies grounded in humanistic values and human rights principles. This study focus on : (1) How are humanistic and professional law enforced by the police? (2) What strategies can be optimised to strengthen the police’srole in upholding humanism and professionalism in law enforcement? This study aims to analyse the implementation of law enforcement by the Indonesian National Police through the lens of humanism and professionalism, while proposing strategic steps to optimise their role based on human rights protection and public trust. The methodology combines normative empirical legal research with statutory, conceptual, and comparative approaches, supported by field data collected through interviews and document analysis. Findings indicate that, despite the presence of a normative framework, implementation remains hindered by weak internal oversight, inadequate human rights training, and institutional resistance. This study offers a multidimensional reform strategy involving police education curriculum transformation, human rights-based performance evaluation, and strengthened external oversight. Also provides a valuable reference for global legal scholars and practitioners seeking models of institutional reform in police organizations, particularly in contexts where democratic values intersect with coercive authority.